2020
DOI: 10.5144/0256-4947.2020.316
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid surgery in 103 children in a single institution from 2000-2014

Abstract: BACKGROUND: Data on thyroid surgery in children are scarce. OBJECTIVE: Analyze outcome data on thyroid surgery in a pediatric population. DESIGN: Medical record review. SETTING: Tertiary health care institution. PATIENTS AND METHODS: We collected demographic and clinical data on patients 18 years or younger who had th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 33 publications
3
29
2
Order By: Relevance
“…A recent pediatric study found that malignancy significantly increased the risk of permanent hypoparathyroidism, while there was no significantly increased risk with Graves' disease 11 . Conversely, another study found that Graves' disease did increase the risk for hypocalcemia 4,36 . Of note, there is a relatively low rate of thyroidectomy for Graves' disease in our study, limiting the power to assess contribution to outcome.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…A recent pediatric study found that malignancy significantly increased the risk of permanent hypoparathyroidism, while there was no significantly increased risk with Graves' disease 11 . Conversely, another study found that Graves' disease did increase the risk for hypocalcemia 4,36 . Of note, there is a relatively low rate of thyroidectomy for Graves' disease in our study, limiting the power to assess contribution to outcome.…”
Section: Discussioncontrasting
confidence: 72%
“…The risk of permanent hypoparathyroidism ranges from 0.6% to 7.3% 4,11,30,36,49,50 . Our experience suggested a higher rate.…”
Section: Discussionmentioning
confidence: 64%
“…And a near-TT or TT can greatly reduce the risk of recurrence and subsequent second surgery. 10 , 11 TT can also optimize or reduce the utilization of postoperative 131 I treatment, and benefits serum Tg as tumor marker to detect recurrent or persistent lesions. In the present study, the bilateral and multifocal lesions were 25.93% and 31.48%, respectively, which was lower than that quoted in ATA children guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 ATA pediatric guidelines recommended TT for the majority of children with PTC. The rationale for this recommendation is based on multiple studies showed an increased incidence of bilateral and multifocal lesions (30% and 65%, respectively) [16,17], while a near-TT or TT can greatly reduce the risk of recurrence and subsequent second surgery [18][19][20]. TT can also optimize or reduce the utilization of postoperative 131 I treatment, and bene ts serum Tg as tumor marker to detect recurrent or persistent lesions.…”
Section: Discussionmentioning
confidence: 99%
“…According to ATA adult guidelines [8], NCCN guidelines(Version 2.2020)and ATA pediatric guidelines [11], Although TT is recommended for the majority of children with PTC, the extent of thyroidectomy is still controversial. The main problem is the in uence of surgical resection scope on tumor recurrence and potential complications (such as transient/permanent postoperative hypoparathyroidism and recurrent laryngeal nerve injury) [19,20,23,24]. Wang et al [25] reported that TT can not reduce recurrence, but only increase the surgical complications.…”
Section: Discussionmentioning
confidence: 99%